Bicycle mystery - Warner, Gertrude Chandler, 1890-1979.; Cunningham, David, 1938- (Chicago : Albert Whitman, 1990)
Four young people find a lost pedigreed dog on a bicycle trip and, while trying to find its home, run into dog thieves.
Reprint. Originally published: 1970.
450
Accelerated Reader AR
Keywords: Dogs -- Fiction